Ion-scale transition of plasma turbulence: Pressure-strain effect - Hellinger,P; Montagud-Camps,V; Franci,L; Matteini,L; Papini,E; Verdini,A; Landi,S (2022)
We investigate properties of solar-wind like plasma turbulence using direct numerical simulations. We analyze the transition from large (magnetohydrodynamic) scales to ion ones using two-dimensional hybrid (fluid electrons, kinetic ions) simulations of decaying turbulence. To quantify turbulence properties we apply spectral transfer and Karman-Howarth-Monin equations for extended compressible Hall MHD to the simulated results. The simulation results indicate that the transition from MHD to ion scales (the so called ion break) results from a combination of an onset of Hall physics and of an effective dissipation owing to the pressure-strain energy-exchange channel and resistivity. We discuss the simulation results in the context of the solar wind.